Production and characterisation of corn chaff briquette using cassava starch and gum Arabic as binders (Agriculture, Food, and Natural Resources Journal, 2024)
This study was undertaken to determine the production and characterisation of corn chaff briquettes using cassava starch and gum Arabic binder. The wet corn chaff was sun-dried to a moisture content of 12%; it was milled using a hammer miller and sieved using a 2 mm particle-size mesh screen for consistency purposes. The briquette samples were produced by separately mixing 60 g of corn chaff with starch and gum Arabic at binder levels 10, 15, and 20 g. The experiment was conducted to determine physical properties (density, moisture content, stability, and shatter index) and proximate analysis (volatile matter, ash content, fixed carbon, and calorific value). The data collected was analysed using Analysis of Variance (ANOVA) in a completely randomized design (CRD) at p
Keywords: Ash content; Calorific value; Corn chaff; Moisture content